Psychosocial Cardiological Schedule-Revised (PCS-R) in a Cardiac Rehabilitation Unit: Reflections Upon Data Collection (2010–2017) and New Challenges - Granata, Nicolò; Nissanova, Ekaterina; Torlaschi, Valeria; Ferrari, Marina; Vigorè, Martina; Sommaruga, Marinella; Angelino, Elisabetta; Rizza, Claudia; Caprino, Alessandra; Pierobon, Antonia (Frontiers in Psychology, 2020)
Introduction: The Psychosocial-Cardiological Schedule (PCS) was developed as a screening tool for patients undergoing cardiac rehabilitation (CR) to detect clinically relevant psychosocial/cognitive problems requiring psychological assessment/intervention. Filled out by a trained nurse, it classifies patients according to their need or not for a psychological interview and intervention provided by the psychologist (PCS-Yes vs. PCS-No). Aims: The main aim was to compare PCS data collected respectively in 2010 and 2017, regarding patients’ socio-demographic characteristics, clinical variables and the inclusion criteria for psychological counseling. Subsequently, the original Italian PCS was revised and an English version of the schedule was provided (Psychosocial Cardiological Schedule-Revised, PCS-R). Results: 28 patients (aged 53.5+12.6 years, M=20) of the 87 recruited in 2010 vs. 35 (aged 64.9+12.7 years, M=28) of the 83 recruited in 2017 met the criteria for PCS-Yes: age<55 years, social problems (living alone, no social support), manifest psychological/behavioral problems, suspected neuropsychological disorders, low prescription adherence, inadequate disease awareness. Comparing the two samples (2010 vs. 2017), clinical variables were similar, and the need for a psychological interview did not differ substantially (32.2% vs. 42.2%), but age increased significantly (PCS-Yes: 53.5±12.6 vs. 64.9±12.7 years, p=0.001; PCS-No: 68.3±8.0 vs. 75.0±7.7 years, p=0.0001). A significant increase was observed in the recommendation for neuropsychological assessment (3.6% vs. 25.7%, p=0.02) to confirm eventual cognitive deficits. These results, the clinical experience and the recent evidences from literature led to the PCS-R, incorporating a psychosocial screening, a psychological/neuropsychological deeper assessment, and a recommendation for a specific intervention to be carried out either during rehabilitation or in outpatient services. Conclusions: The data comparison highlight changes in the cardiac population, which is aging and more frequently requires neuropsychological assessment. The PCS-R could be considered in clinical practice as a useful screening tool to implement a timely coordinated interdisciplinary intervention, comprehensive of specific and tailored psychotherapeutic techniques.